2016
DOI: 10.1002/alr.21873
|View full text |Cite
|
Sign up to set email alerts
|

Sinus surgery can improve quality of life, lung infections, and lung function in patients with primary ciliary dyskinesia

Abstract: We demonstrated an improvement in CRS-related symptoms after ESS and adjuvant therapy. In selected PCD patients, the suggested regimen may postpone chronic lung infection with P. aeruginosa and stabilize lung function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 39 publications
1
49
0
3
Order By: Relevance
“…Among the remaining 163 studies, 37 were either conference abstracts only or it was not possible to find the full text. After reading the full text of the remaining 126 studies, we excluded another 102 articles (Figure 1), including 34 that had overlapping study populations [1850]. We finally included 24 studies reporting spirometric indices of PCD patients in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Among the remaining 163 studies, 37 were either conference abstracts only or it was not possible to find the full text. After reading the full text of the remaining 126 studies, we excluded another 102 articles (Figure 1), including 34 that had overlapping study populations [1850]. We finally included 24 studies reporting spirometric indices of PCD patients in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…These manuscripts included one prospective single-arm trial [13], one retrospective cohort study [14], one cross-sectional study [7], two case series [15,16], and one case report [17]. The number of people included in each study ranged from one to 44.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study developed a metric to assess health-related quality of life in adults with PCD [27], demonstrating the multi-dimensional effects of the disease, including treatment burden and its effects on social and emotion functioning. Endoscopic sinus surgery (ESS) has been shown to help improve quality of life, lung infections, and lung function in adults with PCD [13], and the performance of ESS demonstrated benefit to children with PCD in one study [28], but outcomes in both children and adults are poorly defined, with high variation from study to study. The rarity of the disease makes long-term prospective studies difficult to perform, highlighting the need for multicenter data sharing.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to CF, the sinuses might act as a bacterial reservoir in PCD [73] and therefore bacterial eradication through endoscopic sinus surgery might prove beneficial. ALANIN et al [74] reported a significant improvement in health-related QoL SNOT-22 score after endoscopic sinus surgery and adjuvant treatment (i.e. saline nasal rinsing, topical steroids and 2 weeks of antibiotic treatment).…”
Section: Upper Airway Managementmentioning
confidence: 99%